Representations on adherence to the treatment of Multidrug-Resistant Tuberculosis - Kuitéria Ribeiro Ferreira; Giovanna Mariah Orlandi; Talina Carla da Silva; Maria Rita Bertolozzi; Francisco Oscar de Siqueira França; Amy Bender (SciELO, 2018)
ABSTRACT Objective: To identify representations regarding adherence to the treatment of multidrug-resistant tuberculosis from the perspective of patients who were discharged upon being cured. Method: A qualitative study with patients who completed the drug treatment for multidrug-resistant tuberculosis in São Paulo. Social Determination was used to interpret the health-disease process, and the testimonies were analyzed according to dialectical hermeneutics and the discourse analysis technique. Results: Twenty-one patients were interviewed. The majority (80.9%) were men, in the productive age group (90.4%) and on sick leave or unemployed (57.2%) during the treatment. Based on the testimonies, three categories associated with adherence to treatment emerged: the desire to live, support for the development of treatment and care provided by the health services. Conclusion: For the study sample, adherence to the treatment of multidrug-resistant tuberculosis was related to having a life project and support from the family and health professionals. Free treatment is fundamental for adherence, given the fragilities arising from the social insertion of people affected by the disease. Therefore, special attention is required from the health services to understand patient needs.